A case study of the readability of two grade 4 natural sciences textbooks currently used in South African schools - Sibanda, Lucy (Rhodes University, Faculty of Education, Department of Education, 2013)
This thesis examines the readability of two grade 4 Natural Sciences textbooks currently used in South African schools. Being important sources of classroom input, particularly in grade 4 where learners are reading to learn, textbooks should be readable. That the Natural Sciences subject is only introduced in grade 4 makes the assessment of Natural Sciences textbooks at this level significant. The goal of this research therefore, is to assess the readability of two grade 4 Natural Sciences textbooks and their understandability by learners who speak English as an additional language. The goal of assessing the Natural Sciences textbooks is achieved by the use of cloze and traditional comprehension tests, classic readability formulae, textual analysis and teacher interviews. Cloze and traditional comprehension tests are used to test learners' understanding of the textbooks and classic readability formulae are meant to assess the grade levels of the textbooks. The tests gauge learner understandability while readability formulae establish text readability. Textual analysis allows the assessment of text readability on the basis of more factors than those accommodated by readability formulae. The textual analysis also helps to identify the readability factors supporting or impeding readability. Teacher interviews are conducted to better understand the teachers' perceptions on the readability of the Natural Sciences textbooks. The major findings of the study are that the two Natural Sciences textbooks used in the study are generally above the reading level of the intended readers, grade 4 learners and that the participating learners do not understand these textbooks. The challenges with the readability of the textbooks stem mainly from the vocabulary and concepts used in the textbooks which are not well explained.
Keywords: Science -- Study and teaching (Primary) -- Textbooks; Reading comprehension -- Study and teaching (Primary) -- South Africa; English language -- Textbooks for foreign speakers; English language -- Study and teaching (Primary) -- Foreign speakers; Education, Primary -- South Africa